Rhino-Fodders in Jaldapara Wildlife Sanctuary in Duars of West Bengal, India - Ghosh, Chandrâ; Das, AP (Our Nature, 2008)
Jaldapara Wildlife Sanctuary is the second largest in situ conservatory in India for Rhinoceros unicornis L. As much as 57 species of Rhino-fodders have been recorded from the sanctuary and the list is dominated with the record of 34 species (i.e. 59.65 %) from Poaceae itself. It is followed by five species of Cyperaceae and three species of Euphorbiaceae. Another 13 families are represented with two or one species only. These plants have been categorised into three groups (1) Most Preferred, 15 spp., (2) Preferred, 38 spp. and (3) Stress-time fodders, 4 spp. Local names, habit and edible parts of these plants have been provided in this article. Keywords: Rhino fodder, Jaldapara Wildlife Sanctuary. doi:10.3126/on.v5i1.792 Our Nature (2007)5:14-20